Indole–diterpenoid profiles of Claviceps paspali and Claviceps purpurea from high‐resolution Fourier transform Orbitrap mass spectrometry. (30th July 2014) - Uhlig, Silvio; Egge‐Jacobsen, Wolfgang; Vrålstad, Trude; Miles, Christopher O.
<x xml:space="preserve">Abstract</x> RATIONALE The biological activities most commonly associated with indole–diterpenoids are tremorgenicity in mammals and toxicity in insects through modulation of ion channels. The neurotoxic effects of some analogues are the cause of syndromes such as 'ryegrass staggers' and 'Paspalum staggers' in cattle and sheep. Our purpose was to obtain and interpret mass spectra of some pure Claviceps‐related indole–diterpenoids (paspaline, paspalinine, paxilline, paspalitrems A and B) to facilitate identification of related compounds for which standards were not available. METHODS C. paspali‐infected Paspalum dilatatum as well as C. purpurea sclerotia obtained from infected Phalaris arundinacea were extracted and the extracts separated via liquid chromatography. Low‐ and high‐resolution mass spectra were then obtained of known and potentially unknown indole–diterpenoids. RESULTS At least 20 different indole–diterpenoids were detected in the C. paspali extract with molecular masses ranging from 405 Da (C28H40NO) to 517 Da (C32H40NO5). The C. purpurea sclerotia were shown to contain several indole–diterpenoids with molecular masses ranging from 405 Da (C28H40NO) to 419 Da (C28H38NO2). CONCLUSIONS This study demonstrates for the first time that C. purpurea may also produce indole–diterpenoids. This might explain why grazing of Phalaris spp. is occasionally connected with a tremorgenic syndrome in cattle, called 'phalaris staggers'. Copyright © 2014 John Wiley & Sons, Ltd.